Muhammad Ali Sircar : the first of the world's officially recognized student-author from British India - Rahman, Md. Lutfor, 1949- (Dhaka, Bangladesh : International Publications, 1991)
Biography of Muhammad Ali Sircar, b. 1923, retired civil servant from Bangladesh, who wrote Assam own copy book, a textbook in English for primary students, while he was a student of class X.
Keywords: Sircar, Muhammad Ali, -- 1923-; Civil service -- Bangladesh -- Biography; Authors, bengali -- 20th century -- Biography; English language -- Study and teaching (primary).; Textbooks -- Authorship